Kaka-Tiktok mo yan content and reception analyses on selected Tiktok videos on Martial Law Revisionism - Adante, Britney; Estole, Holly Marie; Solano, Dara Laine A. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
In this plethora of information, the researchers engage in the content, engagement, and discourse analysis of Tiktok videos and discusses the impact of social media, particularly Tik Tok, in the proliferation of historical revisionism and distortion of historical narratives, with a focus on Martial Law revisionism in the Philippines, highlighting the importance of combating disinformation and promoting historical accuracy in the digital age. In conducting this study, the interactions made by active Filipino Tik Tok users were analyzed following the Qualitative Descriptive design. The researchers conducted a qualitative analysis of the videos' content, a reception analysis of the top fifty comments from each video, and developed coding categories to classify audience impact. Theories on Stig Hjarvard?s (2008) notion of Mediatization and Stuart Hall?s (1973) Reception Theory concerning the production and consumption of selected TikTok videos on Martial Law revision were employed. The study functioned on three objectives: 1) analyzing the effectiveness of TikTok videos in promoting historical revisionism, 2) examining audience reactions in the comment section, and 3) assessing the impact of these TikTok videos on the audience.